2019
DOI: 10.3389/fgene.2019.00274
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Autozygosity Derived From Runs of Homozygosity in Jinhua Pigs Disclosed by Sequencing Data

Abstract: Jinhua pig, a well-known Chinese indigenous breed, has evolved as a pig breed with excellent meat quality, greater disease resistance, and higher prolificacy. The reduction in the number of Jinhua pigs over the past years has raised concerns about inbreeding. Runs of homozygosity (ROH) along the genome have been applied to quantify individual autozygosity to improve the understanding of inbreeding depression and identify genes associated with traits of interest. Here, we investigated the occurrence and distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 76 publications
8
45
0
Order By: Relevance
“…This allows mate allocation aiming to minimise inbreeding at the genome level to be achieved more precisely, and the individual animals that have high proportions of ROH coverage to be excluded or used less frequently in mating [16]. The distribution and the occurrence of ROH have been studied in humans [10,11,19,20], cattle [13-15, 18, 21-26], pigs [27][28][29] and sheep [17,[30][31][32] but are poorly studied in some species, for example, in water buffalo.…”
Section: Introductionmentioning
confidence: 99%
“…This allows mate allocation aiming to minimise inbreeding at the genome level to be achieved more precisely, and the individual animals that have high proportions of ROH coverage to be excluded or used less frequently in mating [16]. The distribution and the occurrence of ROH have been studied in humans [10,11,19,20], cattle [13-15, 18, 21-26], pigs [27][28][29] and sheep [17,[30][31][32] but are poorly studied in some species, for example, in water buffalo.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced genomics tools that allow simultaneous genotyping of thousands of polymorphisms across the genome have permitted the identification of long stretches of homozygous genotypes across the genome. These runs of homozygous genotypes were termed “runs of homozygosity” (ROH) and became the subject of several studies investigating animal relatedness and genetic structure of populations (Ferenčaković, Hamzić, et al, 2013; Ferenčaković, Sölkner, & Curik, 2013; Grilz‐Seger et al., 2019; Marchesi et al., 2018; Purfield, Berry, McParland, & Bradley, 2012; Szmatoła et al., 2016; Xu et al., 2019; Yang et al., 2017; Zanella et al., 2016; Zhang, Guldbrandtsen, Bosse, Lund, & Sahana, 2015). By definition, ROH are formed through the inheritance of identical haplotypes from both parents sharing a common ancestor.…”
Section: Introductionmentioning
confidence: 99%
“…For both POP A and B 284 it was possible to identify short and long segments in most of the animals analyzed, whereas 285 in the POP C a small number of animals (n = 7) presented ROH8-16 Mb and none ROH>16 Mb. 286 In recent years, some studies have investigated different genomic methods to estimate 287 inbreeding coefficients in cattle [12,25,26,45,47,48], pigs [27,28,49,50], goats [51][52][53] and 288 rainbow trout [32]. However, this is the first study aimed at characterizing the ROH patterns 289 and comparing different genomic-and pedigree-based methods to estimate inbreeding 290 coefficients in farmed coho salmon populations.…”
Section: Genomics-and Pedigree-based Inbreeding 278mentioning
confidence: 99%
“…Long ROH segments are indicative of recent IBD, whereas short segments indicate ancient 70 inbreeding, and the sum of all these segments are suggested to be an accurate estimation of 71 the inbreeding level of an individual [21]. 72 4 Inbreeding studies using genome-wide data were previously reported in humans 73 [16,22,23], cattle [11,19,[24][25][26], swine [27][28][29], sheep [30], and goats [31]. A recent study 74 reported ROH patterns in rainbow trout populations to show the impact on selection on the 75 genetic diversity in farmed stocks [32].…”
Section: Introduction 33mentioning
confidence: 99%